The role of phosphorylation in mediating cellular responses to DNA damage: the ATM-mediated DNA damage response - Shiloh, Yosef (Henry Stewart Talks, 2011)
Endogenous DNA damage in mammalian cells, DSB repair pathways, Cellular responses to DNA damage, Genomic instability syndromes, Ataxia-telangiectasia, The ATM protein, ATM-mediated DNA damage responses, A SPIKE map, Defective repair of DNA double strand breaks, Allowing repair to happen within chromatin, DNA damage response and the ubiquitin family, Players in ubiquitin-related processes, Phosphoproteome dynamics after DNA damage, Functional networks of phosphorylated proteins, Overlap between Ub, ATM and phosporylation, Functional screens for novel DDR players